Quality Monitoring of Real-Time Precise Satellite Orbit and Clock Corrections for Generating Health Indicators - Xie, Mingqiang; Liu, A.; Wang, N.; El-mowafy, Ahmed; Wang, Z.; Wei, D. (Elsevier, 2025)
The Global Navigation Satellite System (GNSS) Precise Point Positioning (PPP) service provides real-time high precision positioning worldwide. It is essential to monitor precise satellite orbit and clock product quality for early alerts to GNSS users. This paper introduces a server-side method to generate Health Indicators (HI) for satellite corrections. Phase residuals from historical data are modeled as a Residual Hemisphere Map (RHM) to establish monitoring thresholds based on satellite elevation and azimuth. A satellite subset separation scheme is used to identify all faulty satellites by comparing real-time phase residuals with the corresponding thresholds. Tests using data from 30 IGS stations show that the RHM-derived thresholds effectively bound residuals under fault-free conditions. Moreover, the method detects single satellite faults over 5 cm immediately and ramp errors of 1 cm/epoch within 5 epochs, as well as multiple simultaneous faults. The HI generated can be broadcast to users for excluding faulty satellites.